Language development mediates the relationship between gender and relational aggression: A study of Iranian preschool children. (23rd November 2015) - Razmjoee, Maryam; Harnett, Paul H.; Shahaeian, Ameneh
Abstract: Objective: Research has highlighted the role of gender in the expression of aggression. While boys display higher levels of physical aggression, girls appear to display higher levels of relational aggression. It is proposed that the expression of relational aggression may be associated, at least in part, with a child's development of language skills. The aim of the present study was to investigate the role of expressive and receptive language in the expression of relational aggression. Method: A sample of 106 four to six‐year‐old Iranian children completed a test of language ability while their teachers completed a rating scale measuring the children's expression of relational aggression. Results: Results supported the hypothesis that language skills play an important role in the development of relational aggression. Teachers reported that girls displayed significantly more relational aggression that boys. Girls were also found to have higher receptive and expressive language than boys. Finally, a mediation analysis found that language skills mediated the relationship between gender and relational aggression. Conclusions: The results suggest that gender differences in the expression of relational aggression may be related to gender differences in the development of language as opposed to gender per se.